Novel sintered ore and preparation method thereof
By using fine powder and other raw materials with optimized ratio, the alkalinity and utilization rate of the fully refined powder sintered ore is improved, the problem of low sintering efficiency of the whole refined powder is solved, and the production of sintered ore with high drum strength and high RDI (+3.15) is achieved.
Patent Information
- Application Number
- CN202411784049.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, the utilization rate of full-fine powder sintering is relatively low and the efficiency is low.
The basic fine powder is used as the main raw material, combined with white ash, greystone, coke powder, high rebate and self-rebate, and the alkalinity and utilization coefficient of the sintered ore are improved by optimizing the ratio and process flow.
The utilization rate of the sintering of the whole fine powder has been improved, the utilization coefficient of the fine powder reaches 2.0t/m2·h or above, and the drum strength and RDI (+3.15) indicators have been significantly improved.
Smart Images

Figure CN119592788A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of sintering technology, and in particular to a new type of sintered ore and a preparation method thereof. Background Art
[0002] As a blast furnace charge, sintered ore is mainly used in combination with pelletized ore and lump ore to meet the basicity requirements of blast furnace slag. The suitable range of sintered ore basicity is 1.9-2.3. Low basicity will affect the production efficiency of sintered ore and reduce the utilization coefficient. High basicity will cause the quality of sintered ore to deteriorate and the strength to deteriorate. The basicity of sintered ore in most companies is around 2.0. At present, the sintering production metal materials of most companies are mainly made of a combination of domestic refined powder and foreign ore powder. Very few companies use all refined powder for sintering. The efficiency of all refined powder sintering is very low, all at 1.3t / m 2 Peruvian fine powder (Peruvian fine powder) is a high-sulfur magnetic fine powder. There is no precedent of using all Peruvian fine powder for sintering at home and abroad.
[0003] At present, the sintering is mainly based on the metal material structure of domestic refined powder plus foreign ore powder, with a basicity of about 2.0 and a utilization coefficient of 1.6t / m 2 ·h or so (full fine powder sintering does not exceed 1.3t / m 2 h), drum strength about 75%, RDI (+3.15) about 70%. Summary of the invention
[0004] The present application provides a new type of sintered ore and a preparation method thereof to solve the following technical problem: how to improve the utilization rate of sintering of whole fine powder.
[0005] In the first aspect, the present application provides a new type of sintered ore. The raw materials of the new type of sintered ore include, by weight: 50 to 51 parts of fine powder, 6.5 to 7.5 parts of lime, 12 to 13 parts of limestone, 4 to 4.2 parts of coke powder, 10 to 11 parts of high return and 14 to 15 parts of self-return.
[0006] Optionally, the novel sintered ore satisfies at least one of the following properties: drum strength of 81.5% to 82.7%, RDI (+3.15) of 97.5% to 98%, and basicity of 4.9 to 5.2.
[0007] Optionally, the utilization coefficient of the secret fine powder is 2.0t / m 2 ·h~2.3t / m 2 ·h.
[0008] In a second aspect, the present application provides a method for preparing the novel sintered ore described in the first aspect, the method comprising:
[0009] According to the weight proportions, the secret fine powder, the white lime, the limestone, the coke powder, the high return and the self-return are mixed to obtain a mixture;
[0010] The mixed material is mixed and granulated to obtain material balls;
[0011] The material balls are sequentially distributed, ignited and sintered under negative pressure to obtain sintered ore.
[0012] Optionally, the carbon content of the mixture is 3.4% to 3.5%.
[0013] Optionally, the mixing and granulation time is 80s to 100s.
[0014] Optionally, the water content of the pellets is 6.5% to 7.5%.
[0015] Optionally, the thickness of the sintered material layer of the cloth is 750 mm to 800 mm.
[0016] Optionally, the ignition temperature is 1050°C to 1150°C, the ignition negative pressure is 4kpa to 5kpa, and the ignition time is 80s to 100s.
[0017] Optionally, the negative pressure of the negative pressure sintering is 13 kpa to 15 kpa.
[0018] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0019] The present application provides a new type of sintered ore. The raw materials of the new type of sintered ore include, by weight, 50 to 51 parts of fine powder, 6.5 to 7.5 parts of lime, 12 to 13 parts of limestone, 4 to 4.2 parts of coke powder, 10 to 11 parts of high return and 14 to 15 parts of self-return. All the metal materials in the raw materials are fine powder. The alkalinity of the sintered ore is improved by optimizing the ratio of other components such as lime. The Ca(OH)2 colloidal particles formed by the digestion of the high-alkalinity sintered ore raw materials with water have strong water absorption, which helps to reduce the over-wetting phenomenon of the sintering material layer. The digestion of lime is an exothermic reaction, which helps to increase the material temperature and improve the air permeability of the sintered ore, so that the utilization coefficient of fine powder sintering reaches 2.0t / m 2 ·h or more, thus improving the utilization rate of all refined powder sintering. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0021] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0022] Figure 1 A schematic flow chart of a novel method for preparing sintered ore provided in an embodiment of the present application. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0024] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range; for example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which applies regardless of the range; in addition, whenever a numerical range is indicated in this document, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0025] In this document, the terms including "including" and "including" mean "including but not limited to". Relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. "And / or" describes the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone; where A and B can be singular or plural. "At least one" means one or more, and "plurality" means two or more; "at least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single or plural items; for example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, if the weight ratio of substance A, substance B and substance C is 1:2:3, then substance A, substance B and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the weight of substance A: the weight of substance B: the weight of substance C = 1:2:3.
[0026] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this article can be purchased from the market or prepared by existing methods.
[0027] In the first aspect, the present application provides a new type of sintered ore. The raw materials of the new type of sintered ore include, by weight: 50 to 51 parts of fine powder, 6.5 to 7.5 parts of lime, 12 to 13 parts of limestone, 4 to 4.2 parts of coke powder, 10 to 11 parts of high return and 14 to 15 parts of self-return.
[0028] Secret fine powder is a high-sulfur, low-silicon magnetic fine powder, with a -200 mesh size accounting for more than 80%. The particle size is extremely fine and belongs to a fine powder ore. Because it is not easy to form a ball, it is traditionally considered to be unfavorable for improving the sintering utilization coefficient; at the same time, the high sulfur content will increase the external sulfur discharge and affect the environmental protection. Secret fine powder is rarely used in the sintering process, and even if it is used, the ratio is very low and will not exceed 2%. In the embodiment of the present application, secret fine powder is used as one of the main raw materials, which not only utilizes its iron content, but also controls sulfur emissions through subsequent processes. Exemplarily, the weight parts of secret fine powder can be 50 parts, 50.2 parts, 50.4 parts, 50.6 parts, 50.8 parts, 51 parts, etc.
[0029] White ash is the product of calcined limestone, with a CaO content of more than 80%. After being digested with water, white ash becomes colloidal particles with extremely fine particle size, which has extremely strong water absorption. Ca(OH)2 colloidal particles can pull ore particles closer, generate necessary capillary force, promote the combination of material particles, and form small balls. In addition, the digestion of white ash is an exothermic reaction. For every 1% increase in the white ash ratio, the material temperature can be increased by 2.7°C, which helps to reduce the over-wetting phenomenon of the sintering material layer, improve air permeability, and improve the sintering utilization coefficient. White ash weight exceeding 7.5 parts is easy to cause the mixer and material trough to stick, affecting normal production. In addition, the weight of white ash is 6.5 to 7.5 parts, which can increase the basicity of the sintered ore, is conducive to sintering sulfur fixation, and reduces the sulfur content in the sintering flue gas. Exemplarily, the weight of white ash can be 6.5 parts, 6.7 parts, 6.9 parts, 7.1 parts, 7.3 parts, 7.5 parts, etc.
[0030] Limestone refers to the product obtained after calcining limestone. It is rich in CaO and plays a vital role in the sintering process. It is not only the main source of alkaline oxides, but also helps to increase the alkalinity of the sintered ore, thereby affecting the reducibility and metallurgical properties of the sintered ore. Limiting the weight of limestone to 12 to 13 parts can ensure that there is a sufficient supply of alkaline oxides during the sintering process, promote the formation of the sintered ore and the stability of the structure, while avoiding excessive addition. Over-melting or performance degradation of the sintered ore. Exemplarily, the weight of limestone can be 12 parts, 12.2 parts, 12.4 parts, 12.6 parts, 12.8 parts, 13 parts, etc.
[0031] As the main fuel in the sintering process, the amount of coke powder has a direct impact on the sintering temperature, sintering speed and quality of the sintered ore. Limiting the weight of coke powder to 4 to 4.2 parts can ensure sufficient heat supply during the sintering process, while avoiding problems such as over-melting or incomplete sintering of the sintered ore caused by excess heat. This helps to optimize the sintering process and improve the output and quality of the sintered ore. Exemplarily, the weight of coke powder can be 4 parts, 4.05 parts, 4.1 parts, 4.15 parts, 4.2 parts, etc.
[0032] High return is the return material from the blast furnace, including pellets, lump ore and sintered ore, with the main components being TFe, CaO and SiO 2. Gaofan has undergone one or more sintering processes, and its chemical composition and physical properties are relatively stable. Limiting the weight of Gaofan to 10 to 11 parts can ensure the consistency of the composition of the sintered ore, thereby helping to stabilize the overall performance of the sintered ore. By rationally utilizing Gaofan, the demand for new raw materials can be reduced and the overall utilization of resources can be improved. This not only helps to reduce production costs, but also helps to reduce the impact on the environment and achieve green production. In addition, the addition of Gaofan can change the particle size distribution of the sintering material, thereby improving the permeability during the sintering process. Good permeability helps the gas and heat in the sintering material to transfer more efficiently, promotes the sintering reaction, and improves the quality of the sintered ore. Exemplarily, the weight of Gaofan can be 10 parts, 10.2 parts, 10.4 parts, 10.6 parts, 10.8 parts, 11 parts, etc.
[0033] Self-return (self-return material) is -5mm sintered ore produced in the sintering process, and its main components are TFe, CaO and SiO 2 By limiting the weight of the self-return to 14 to 15 parts, the existing raw materials can be used to the maximum extent, and the dependence on new raw materials can be reduced, thereby improving the overall utilization rate of raw materials. Exemplarily, the weight of the self-return can be 14 parts, 14.2 parts, 14.4 parts, 14.6 parts, 14.8 parts, 15 parts, etc.
[0034] In some embodiments, the novel sintered ore meets at least one of the following properties: drum strength of 81.5% to 82.7%, RDI (+3.15) of 97.5% to 98%, and basicity of 4.9 to 5.2.
[0035] In the field of material testing, drum strength refers to the material's ability to resist crushing and wear in a drum test. In the new sintered ore, the drum strength ranges from 81.5% to 82.7%, which means that after the drum test, most of the sintered ore particles (81.5% to 82.7%) can remain intact and not broken. High drum strength indicates that the sintered ore has good mechanical strength and wear resistance, which is crucial for the stability and permeability of the material layer during blast furnace smelting. Exemplarily, the drum strength of the new sintered ore can be 81.5%, 81.7%, 81.9%, 82.1%, 82.3%, 82.5%, 82.7%, etc.
[0036] RDI is the low-temperature reduction pulverization index. RDI (+3.15) indicates the change in the pulverization rate of sintered ore with a particle size of less than 3.15 mm during low-temperature reduction under certain conditions. RDI (+3.15) is one of the important indicators for evaluating the quality of sintered ore. It reflects the pulverization performance of sintered ore during low-temperature reduction. The lower the pulverization rate, the better the pulverization resistance of the sintered ore and the higher the quality. During the blast furnace production process, the pulverization of sintered ore will seriously affect the permeability of the upper part of the blast furnace, thereby affecting the smooth operation and output of the blast furnace. Therefore, by testing RDI (+3.15), the pulverization performance of the sintered ore can be understood and guidance can be provided for blast furnace production. By testing the RDI (+3.15) value of sintered ore under different process conditions, the sintering process parameters, such as batching ratio, sintering temperature and time, can be optimized to improve the quality and output of the sintered ore. For example, the RDI (+3.15) of the novel sintered ore may be 97.5%, 97.6%, 97.7%, 97.8%, 97.9%, 98%, etc.
[0037] Basicity is an indicator to measure the ratio of basic oxides to acidic oxides in sintered ore. It reflects the chemical composition and mineral composition of the sintered ore. In the embodiments of the present application, the basicity of the new sintered ore can be 4.9, 4.95, 5.0, 5.05, 5.1, 5.15, 5.2, etc.
[0038] In some embodiments, the utilization coefficient of the secret fine powder is 2.0t / m 2 ·h~2.3t / m 2 ·h.
[0039] Due to the fine particle size and high assimilation temperature of refined powder, the use of high proportion of refined powder for sintering is likely to result in low sintering production efficiency. Currently, the utilization coefficient of all refined powder sintering does not exceed 1.3t / m 2 h. The utilization coefficient of the ultra-high basicity sintered ore produced in the examples of this application is 2.0 t / m 2 ·h~2.3t / m 2 ·h. For example, the utilization factor of the secret fine powder can be 2.0t / m 2 h, 2.05t / m 2 h, 2.1t / m 2 h, 2.15t / m 2 ·h, 2.2t / m 2 h, 2.25t / m 2 ·h, 2.3t / m 2 ·h, etc.
[0040] Figure 1 A schematic flow chart of a novel method for preparing sintered ore provided in an embodiment of the present application.
[0041] See also Figure 1 In a second aspect, the present application provides a method for preparing the novel sintered ore described in the first aspect, the method comprising:
[0042] S1. Mix the secret fine powder, the lime, the limestone, the coke powder, the high return and the self-return according to the weight parts to obtain a mixture;
[0043] S2, mixing and granulating the mixed material to obtain pellets;
[0044] S3, placing, igniting and negative pressure sintering the material balls in sequence to obtain sintered ore.
[0045] In some embodiments, the carbon content of the mixture is 3.4% to 3.5%.
[0046] Carbon content is a key factor in the reducibility of sintered ore. During the sintering process, carbon, as a reducing agent, can react with the oxides in the mixture to generate metallic iron and other reduction products. Controlling the carbon content of the mixture within the range of 3.4% to 3.5% can ensure the full progress of the reduction reaction, improve the reducibility and metallization rate of the sintered ore, and thus meet the requirements of blast furnace ironmaking for reducibility. A carbon content of 3.4% to 3.5% helps to form a stable sintered ore structure and improve the strength and wear resistance of the sintered ore. If the carbon content is higher than 3.5%, it will cause excessive reducing atmosphere to be generated during the sintering process, causing excessive free carbon and cementite to appear in the sintered ore, reducing the strength and wear resistance of the sintered ore. Controlling the carbon content within the range of 3.4% to 3.5% can avoid such adverse effects and improve the overall quality of the sintered ore. Exemplarily, the carbon content of the mixture can be 3.42%, 3.44%, 3.46%, 3.48%, 3.5%, etc.
[0047] In some embodiments, the mixing and granulation time is 80s to 100s.
[0048] Mixing granulation is a key link in the sintering process. Through mixing granulation, the raw materials can be mixed twice, and water can be added to the balls to obtain sintering materials with suitable particle size and good air permeability. Controlling the time of mixing granulation within 80s to 100s can ensure that the raw materials are fully mixed and evenly balled, thereby optimizing the particle size distribution of the sintering material and making it more uniform. The mixing granulation time of 80s to 100s helps to fully distribute the moisture and binder in the raw materials to form a compact and stable ball structure. This structure is conducive to gas permeation and heat transfer during the sintering process, thereby improving the sintering efficiency and enabling the sintered ore to reach the required temperature and structural strength faster. Exemplarily, the time of mixing granulation can be 80s, 84s, 88s, 92s, 96s, 100s, etc.
[0049] In some embodiments, the moisture content of the pellets is 6.5% to 7.5%.
[0050] A water content of 6.5% to 7.5% can ensure that the ball has good air permeability during the sintering process, which helps gas exchange and heat transfer during the sintering process. Balls with good air permeability can be heated more evenly during sintering, thereby improving the overall quality of the sintered ore. In addition, moisture plays a role in lubrication and heat transfer during the sintering process, which helps the chemical reaction and physical bonding between the raw materials. 6.5% to 7.5% moisture can promote the reduction reaction and melting process of iron ore, thereby improving the strength and reducibility of the sintered ore. Exemplarily, the water content of the ball can be 6.5%, 6.7%, 6.9%, 7.1%, 7.3%, 7.5%, etc.
[0051] In some embodiments, the thickness of the sintered material layer of the cloth is 750 mm to 800 mm.
[0052] The sintering material layer thickness of 750mm to 800mm can ensure the smooth flow of gas in the material layer, thereby improving the permeability. A material layer with good permeability is conducive to gas exchange and heat transfer during the sintering process, and promotes the uniform progress of the sintering reaction. Within the limited material layer thickness range, the sintering material can be heated more evenly to avoid local overheating or insufficient temperature. This helps to obtain sintered ore with uniform structure and stable performance. The material layer thickness of 750mm to 800mm can also optimize the energy utilization in the sintering process and reduce unnecessary energy consumption. A thicker material layer may cause heat transfer to be blocked and increase energy consumption; while a thinner material layer may make the sintering process insufficient, which also affects energy consumption and product quality. Exemplarily, the thickness of the sintering material layer can be 750mm, 760mm, 770mm, 780mm, 790mm, 800mm, etc.
[0053] In some embodiments, the ignition temperature is 1050° C. to 1150° C., the ignition negative pressure is 4 kPa to 5 kPa, and the ignition time is 80 s to 100 s.
[0054] Ignition temperature is a key parameter in the sintering process, which directly affects whether the mixture can be ignited smoothly and form a stable combustion layer. Limiting the ignition temperature to 1050℃~1150℃ can ensure that the fuel (such as coke powder) in the mixture can be quickly ignited at this temperature and form a stable flame, providing sufficient heat for the subsequent sintering process. The sintering process involves multiple physical and chemical changes, including the combustion of fuel, the melting and bonding of minerals, etc. The ignition temperature of 1050℃~1150℃ can promote the progress of these reactions, especially the full combustion of fuel, which can release more heat, help soften and melt minerals, thereby improving the quality of sintered ore. Exemplarily, the ignition temperature can be 1050℃, 1070℃, 1090℃, 1110℃, 1130℃, 1150℃, etc.
[0055] During the ignition stage, a negative pressure of 4kpa to 5kpa helps reduce the air flow, making the heat in the ignition area more concentrated, thereby accelerating the ignition process. A negative pressure of 4kpa to 5kpa also helps reduce the oxygen supply during the ignition process, preventing excessive combustion due to excessive oxygen in the early stage of ignition, and is conducive to the stable sintering process. Exemplarily, the negative pressure of ignition can be 4kpa, 4.2kpa, 4.4kpa, 4.6kpa, 4.8kpa, 5kpa, etc.
[0056] In some embodiments, the negative pressure of the negative pressure sintering is 13 kPa to 15 kPa.
[0057] During the negative pressure sintering process, the negative pressure generated by the exhaust device under the sintering machine trolley helps to extract the gas in the sintering material layer and maintain good air permeability inside the material layer. Controlling the negative pressure within the range of 13kpa to 15kpa can ensure the smooth flow of gas in the sintering material layer and avoid uneven sintering caused by local gas retention. Good air permeability helps gas exchange during the sintering process, such as the combustion reaction of oxygen and fuel, the reduction reaction of carbon dioxide and ore, etc. During negative pressure sintering, the rapid flow of gas in the material layer can accelerate these reactions, thereby improving the reactivity and quality of the sintered ore. Exemplarily, the negative pressure of negative pressure sintering can be 13kpa, 13.5kpa, 14kpa, 14.5kpa, 15kpa, etc.
[0058] The present application is further described below in conjunction with specific embodiments. The experimental methods in the following embodiments that do not specify specific conditions are usually measured in accordance with national standards / industry standards; if there are no corresponding national standards / industry standards, they are measured in accordance with common international standards, conventional conditions, or conditions recommended by the manufacturer.
[0059] This embodiment provides a method for preparing a novel sintered ore, comprising the following steps:
[0060] According to the weight proportions, the secret fine powder, the white lime, the limestone, the coke powder, the high return and the self-return are mixed to obtain a mixture;
[0061] The mixed material is mixed and granulated to obtain material balls;
[0062] The material balls are sequentially distributed, ignited and sintered under negative pressure to obtain sintered ore.
[0063] The composition (wt%), carbon content and basicity of the mixture are shown in Table 1, and the process parameters of ignition and negative pressure sintering are shown in Table 2.
[0064] Table 1 Composition (wt%), carbon content (wt%) and basicity of the mixture
[0065]
[0066]
[0067] During the sintering process, SO in the sintering flue gas 2 After sintering, the utilization coefficient of the fine powder, sintering index and SO2 emission were tested. 2 The situation is shown in Table 2.
[0068] Table 2 Ignition and negative pressure sintering process parameters, utilization coefficient of fine powder, sintering index and SO emission 2 Condition
[0069]
[0070] As shown in Tables 1 and 2, in the examples, the composition of the mixture and the sintering process parameters are within the required range of the present invention, and the utilization coefficient of the fine powder reaches 2.0 t / m 2 h, the drum strength of sintered ore reaches 81.6%, RDI (+3.15) reaches 97.7%, and SO in sintering flue gas 2 Concentration less than 700mg / mg 3 .
[0071] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0072] In the embodiment of the present invention, all metal materials are made of fine powder, and the utilization coefficient reaches 2.0t / m 2 ·h or more, which is 30% higher than ordinary sintering and 50% higher than full-fine powder sintering, solving the problem of low production efficiency of full-fine powder sintering.
[0073] The embodiment of the present invention uses all-secret powder for sintering, and SO in the sintering flue gas is 2 Concentration less than 700mg / mg 3, which solves the problem of SO in desulfurized flue gas caused by using high proportion of fine powder 2 The problem of high content.
[0074] The ultra-high basicity sintered ore produced by the embodiment of the present invention has a basicity of 5.0 and can ensure a grade of more than 53%.
[0075] The above is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. It will be apparent to those skilled in the art that various modifications to these embodiments are possible, and the general principles defined in the present application can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to these embodiments shown in the present application, but will conform to the widest scope consistent with the principles and novel features applied for by the present application.
Claims
1. A novel sintered ore, wherein the raw materials of the novel sintered ore include, by weight: 50 to 51 parts of secret powder, 6.5 to 7.5 parts of lime, 12 to 13 parts of limestone, 4 to 4.2 parts of coke powder, 10 to 11 parts of high return and 14 to 15 parts of self return.
2. The novel sintered ore according to claim 1, characterized in that: The novel sintered ore meets at least one of the following properties: drum strength of 81.5% to 82.7%, RDI (+3.15) of 97.5% to 98%, and basicity of 4.9 to 5.
2.
3. The novel sintered ore according to claim 1, characterized in that: The utilization coefficient of the secret fine powder is 2.0t / m 2 ·h~2.3t / m 2 ·h.
4. A method for preparing the novel sintered ore according to any one of claims 1 to 3, the method comprising: According to the weight proportions, the secret fine powder, the white lime, the limestone, the coke powder, the high return and the self-return are mixed to obtain a mixture; The mixed material is mixed and granulated to obtain material balls; The material balls are sequentially distributed, ignited and sintered under negative pressure to obtain sintered ore.
5. The method according to claim 4, characterized in that The carbon content of the mixture is 3.4% to 3.5%.
6. The method according to claim 4, characterized in that The mixing and granulation time is 80s to 100s.
7. The method according to claim 4, characterized in that The water content of the ball is 6.5% to 7.5%.
8. The method according to claim 4, characterized in that The thickness of the sintered material layer of the cloth is 750 mm to 800 mm.
9. The method according to claim 4, characterized in that The ignition temperature is 1050° C. to 1150° C., the ignition negative pressure is 4 kpa to 5 kpa, and the ignition time is 80 s to 100 s.
10. The method according to claim 4, characterized in that The negative pressure of the negative pressure sintering is 13kpa-15kpa.